Addressing fidelity within complex health behaviour change interventions: A protocol of a scoping review of intervention fidelity frameworks and models. [version 1; peer review: 2 approved] - Rebekah Roy (HRB Open Research, 2018)
Intervention fidelity is crucial to facilitate accurate interpretation of research outcomes, but has been inadequately addressed within complex health behaviour change interventions. Recent research has highlighted a need for practical guidance to improve understanding and use of existing fidelity frameworks and models within complex health behaviour change intervention research. The aim of this paper is to present a protocol for a scoping review of existing intervention fidelity frameworks and models.  In accordance with scoping review guidelines, the following stages will be conducted: (1) identifying the research question, (2) identifying potentially relevant studies of fidelity frameworks and models, (3) study screening and selection, (4) charting and extracting data from identified frameworks and models, (5) collating, summarising and reporting the results and (6) consultation with stakeholders. Two reviewers will independently conduct the screening and extraction stages. Identified frameworks will be collated, summarized and categorized iteratively by one reviewer in consultation with the review team. The findings of this review will provide a useful resource by identifying and comparing existing fidelity frameworks and models. It is intended that increased clarity and understanding in this area will facilitate the appropriate selection and application of fidelity frameworks for complex health behaviour change interventions, inform areas for future research, and ultimately contribute towards improving how intervention fidelity is addressed in this area.